2008
DOI: 10.1016/j.nuclphysb.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

PeV scale Left–Right symmetry and baryon asymmetry of the Universe

Abstract: We study the cosmology of two versions of supersymmetric Left-Right symmetric model. The scale of the B − L symmetry breaking in these models is naturally low, 10 4 − 10 6 GeV. Spontaneous breakdown of parity is accompanied by a first order phase transition. We simulate the domain walls of the phase transition and show that they provide requisite conditions, specifically, CP violating phase needed for leptogenesis. Additionally soft resonant leptogenesis is conditionally viable in the two models considered. So… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 73 publications
(106 reference statements)
0
35
0
Order By: Relevance
“…It was shown that this model breaks down to minimal supersymmetric standard model (MSSM) at low scale. This model was studied in the context of cosmology in [39,51] specifically, the mechanism for leptogenesis via Domain Walls in [40].…”
Section: Minimal Supersymmetric Left-right Model : a Recapmentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that this model breaks down to minimal supersymmetric standard model (MSSM) at low scale. This model was studied in the context of cosmology in [39,51] specifically, the mechanism for leptogenesis via Domain Walls in [40].…”
Section: Minimal Supersymmetric Left-right Model : a Recapmentioning
confidence: 99%
“…Since the original theory is parity invariant a second solution for the F and D flat conditions exists, with Left type fields' vev's exchanged with those of the Right type fields [39,40].…”
Section: Minimal Supersymmetric Left-right Model : a Recapmentioning
confidence: 99%
See 3 more Smart Citations